2007
DOI: 10.1063/1.2820387
|View full text |Cite
|
Sign up to set email alerts
|

Trace gas detection using nanostructured graphite layers

Abstract: Nanostructured graphite (NG) has been investigated as a sensing material using a highly sensitive potentiometric detection technique. NO2 concentration down to 60ppb was detected in ambient conditions using NG functionalization layer. Simultaneous current and surface work function (SWF) change transients measured using NG functionalization layer reveal much shorter response time for the later, which is attributed to its dependence solely on surface molecular adsorption. The gradient of SWF with respect to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 14 publications
0
37
0
6
Order By: Relevance
“…35,[42][43][44][45][46][47][48] Furthermore, humidity enhances hole doping by O 2 . 49 Sque et al specifically suggested that graphene could undergo transfer doping to the aqueous oxygen redox couple.…”
Section: Discussionmentioning
confidence: 99%
“…35,[42][43][44][45][46][47][48] Furthermore, humidity enhances hole doping by O 2 . 49 Sque et al specifically suggested that graphene could undergo transfer doping to the aqueous oxygen redox couple.…”
Section: Discussionmentioning
confidence: 99%
“…В работах [8,9] были проведены одновременные изме-рения G и φ, наводимые молекулами NO 2 , NH 3 , паров воды, ацетона и метанола, адсорбированными на много-слойной пленке наноструктурированного графита (НГ), содержащей как кристаллические, так и аморфные обла-сти. При этом анализировалось отношение…”
Section: адсорбция на наноструктурированном графитеunclassified
“…В [14] также определялись значения φ при адсорбции NO 2 и NH 3 : в первом случае значения φ для обеих граней отрицательны, тогда как во втором положительны. Отсюда следует, согласно (2), что NO 2 является донором, а NH 3 акцептором, что противоречит всем предыдущим результатам по адсорб-ции на углеродных наноструктурах [8][9][10][11][12][13]. В связи с этим отметим, что в работе [15] те же знаки изменения Журнал технической физики, 2017, том 87, вып.…”
Section: адсорбция на графенеunclassified
See 1 more Smart Citation
“…The mechanism of action for G-FET sensors is that chemical species adsorbed on the surface of the graphene act as electron donors or acceptors, resulting in conductance changes. Most of the graphene sensors have been used to detect gas molecules (Arsat et al, 2009;Dan et al, 2009;Fowler et al, 2009;Lu et al, 2009;Qazi et al, 2007;Robinson et al, 2008;Schedin et al, 2007). In addition, research on electrical detection of biomolecule detection using graphene has gradually increased over the last few years.…”
mentioning
confidence: 99%